-6x+7x=3

Simple and best practice solution for -6x+7x=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+7x=3 equation:


Simplifying
-6x + 7x = 3

Combine like terms: -6x + 7x = 1x
1x = 3

Solving
1x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '1'.
x = 3

Simplifying
x = 3

See similar equations:

| 2[x+8]=-6x-14 | | 3.1=4.9-0.9x | | 5=m-5(4) | | 12t-22=5t-1 | | (4u+2)(9+u)=0 | | (1/3)(x+4)=2x-3 | | -10+d=9-6d+9 | | 5x-1=14x-69 | | 3a+1=-3.6 | | 5t-2y=7 | | 3x+4x-8=27 | | 4e^7x=7e^9x | | 3x+4y=123 | | (15x+-43)+(8x+18)=90 | | 4(x-3)+5x=-52+x | | 3(x-1)=2+.05x | | (n+5)(n-9)=18 | | x^2+3x=400 | | 9+-3k=17+2k | | 0=x^2-6x+13 | | 10=x(x+3) | | -10=8+9x | | 6(2x-3)+4(7-x)=26 | | -1/4+1/2=1/4x-5/8 | | 18x^2+5+15=0 | | 400=x(x+3) | | 4(3x+1)=3(5x-4) | | R=5m+n | | 0.06(x-10)=0.03x | | 5(8x+7)=35 | | 16=p+8-5p | | T-(-16)=19 |

Equations solver categories